Chinese Investment in U.S. Real Estate Markets Using the EB-5 Program. (February 2016) - Simons, Robert A.; Wu, Jing; Xu, Jie; Fei, Yu
EB-5 is a U.S. immigrant-attraction program created in the early 1990s. After lying mostly dormant, it recently became a source of gap capital when the lending markets collapsed during the Great Recession of 2008 to 2012. With low loan-to-value ratios and high capitalization rates for real estate projects at the end of the Great Recession, the EB-5 investor visa program has been instrumental in filling the financing gap, especially for hotels. Most EB-5 investors are Chinese. We focus primarily on Chinese investor attitudes toward the program, using a nonrandom survey of 85 potential investors who invested in projects in Cleveland, Ohio. The survey was administered in Chinese. Our survey found that Chinese wealthy private business owners are mainly participants in EB-5 for acquiring a U.S. green card on behalf of their young adult children. The rate of return of the EB-5 program for investors is a low-priority item, less important than return of capital.